2017
DOI: 10.5539/jms.v7n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Business Practices in the United States: A Survey on Implementation

Abstract: A survey was designed and administered to 172 business professionals in the United States in 2015 to obtain their assessments of both the current status and future development of sustainable business practices at their companies. Despite the recent attention given to corporate social responsibility, we find that only 34 percent of respondents have a comprehensive sustainable management plan currently in place. However, the survey indicates that by 2021 that percentage is expected to increase to 54 percent. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…There are various practices that can be applied when a business wants to implement greener behaviors. For instance, the U.S. Small Business Administration (SBA) provides recommendations on several strategies for businesses to explore, including becoming energy efficient, improving waste management, and utilizing renewable energy (Chang and Slaubaugh 2017 ). Ashton et al ( 2017 ) studied the adoption of such green business practices among small manufacturing enterprises in the Greater Chicago area, and found that adopting energy efficiency in facilities, as well as recycling materials such as metal, paper, and plastics, were the most common green practices implemented in these firms.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…There are various practices that can be applied when a business wants to implement greener behaviors. For instance, the U.S. Small Business Administration (SBA) provides recommendations on several strategies for businesses to explore, including becoming energy efficient, improving waste management, and utilizing renewable energy (Chang and Slaubaugh 2017 ). Ashton et al ( 2017 ) studied the adoption of such green business practices among small manufacturing enterprises in the Greater Chicago area, and found that adopting energy efficiency in facilities, as well as recycling materials such as metal, paper, and plastics, were the most common green practices implemented in these firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A similar study by Depken and Zeman ( 2018 ), which focused on SMEs in Iowa, also found that waste reduction and recycling were the most implemented green practices, followed by deploying energy efficiency measures. Chang and Slaubaugh ( 2017 ) studied businesses across the U.S. and found that using less paper, conserving water, and adopting energy efficient technologies, among other green practices, are preferred by the companies they studied, as they have immediate impacts on a firm’s financial benefits.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the advertised strategies and ambitions with regards to sustainability, many organizations struggle to operationalize these strategies into concrete actions (Chang & Slaubaugh, 2017). As projects are a vehicle for the implementation of organizational strategies (Project Management Institute, 2017), the management of projects is now gaining attention as an essential enabler of the transition of organizations towards sustainability (Marcelino-Sádaba et al, 2015;Morris, 2009;Longman & Mullins, 2004).…”
Section: Introducuction Of the Problemmentioning
confidence: 99%